PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP MOTIVASI DAN KINERJA KARYAWAN - Pratini, Perna; Utama, I Wayan Mudiartha (E-Jurnal Manajemen; Vol 5 No 7 (2016), 2016)
ABSTRACT Employee performance is the result of work achieved in implementing the tasks of employees in accordance with the responsibilities given. Motivation is a way of encouraging employees' passion to want to work hard to achieve good performance. The purpose of this study to determine the effect of transformational leadership and organizational culture on the motivation and performance of employees. This research was conducted in C151 to sample as many as 59 employees. The method used is by sampling saturated. Data were collected through interviews and questionnaires. Questionnaires were administered to 59 respondents, to further analyzed using path analysis (path analysis). Based on calculations using the program IBM SPSS Statistics Version 17.0, be concluded transformational leadership and organizational culture has a positive and significant impact on the motivation and performance and motivation has a positive and significant impact on performance. It shows if the better of transformational leadership and organizational culture, the motivation and performance of employees will increase.
Keywords: Keywords: Transformational Leadership, Organizational Culture, Motivation, Performance